Crude glycerin in feedlot cattle diets and as a solvent in Maillard reaction processes intended for manufacturing value-added protein meals - Schneider, Cody James (Kansas State University, 2010)
Two trials were conducted to evaluate effects of crude glycerin, a byproduct of the biodiesel industry, on feedlot performance, carcass characteristics, and diet digestibility in cattle. A third study was conducted to investigate the use of glycerin as a solvent in Maillard reaction processes used to manufacture value added protein meal. In trial 1, crossbred yearling heifers were fed low levels of glycerin (0, 0.5, or 2% of diet DM) in corn finishing diets, or diets that combined corn with soybean hulls and wet distiller’s grains (0 or 2% glycerin). Results indicated that feeding glycerin decreased DMI (P = 0.04), and feeding byproducts increased DMI (P < 0.01) when compared to control without byproducts or glycerin. Feeding byproducts or glycerin decreased the percentage of carcasses that graded USDA Choice or higher (P < 0.05). Other live performance traits and carcass characteristics were similar across treatments. Trial 2 evaluated effects of crude glycerin on growth performance and diet digestibility in heifers fed high forage growing diets. Treatments consisted of 0, 4, or 8% crude glycerin added to growing diets containing corn silage (60% of DM) and wet corn gluten feed. Apparent total tract digestibilities were calculated from total fecal collections. Adding glycerin linearly increased (P = 0.01) feed efficiency over the entire feeding period, and linearly decreased (P = 0.02) DMI for a portion of the feeding period. No other effects of glycerin on animal growth performance were observed. Digestibility measurements indicated that glycerin decreased DM, OM, and NDF intakes linearly (P < 0.01), but did not affect fecal outputs of DM, OM, or NDF. Apparent total tract digestibilities of DM, OM, and NDF therefore decreased linearly (P < 0.01) with increasing levels of glycerin. The third trial involved several experiments, which were conducted to determine if glycerol could be used as a solvent in processes designed to facilitate non-enzymatic browning of protein meals. Results indicated that glycerol may serve as a more suitable solvent for browning processes than water because its chemical and physical properties may enhance browning processes, increase process efficiency, and yield products with superior resistance to microbial degradation.
Keywords: Feedlot Cattle; Glycerin; Agriculture, Animal Culture and Nutrition (0475)